Rekonstruksi Tujuan Hukum dalam Perspektif Hukum Barat dan maqāṣid al-syarī‘ah : Analisis Filosofis terhadap Keadilan, Kemanfaatan, dan Kemaslahatan - Muhammad Zaid Anshari Nasution (Yayasan Dar Arrisyah Indonesia, 2024)
The purpose of law is a fundamental topic of discourse in the philosophy of law and Islamic law because it is directly related to the orientation of norm-setting, the enforcement of justice, and the protection of human interests. This article aims to analyze a comparison of the purposes of law from the perspectives of Western law and Islamic law, emphasizing the relationship between the concepts of justice, legal certainty, utility, and maqāṣid al-syarī‘ah. This study employs a normative legal method with a philosophical and conceptual approach through a literature review of contemporary works on the philosophy of law, ushul fiqh, and maqāṣid al-syarī‘ah. The results of the study indicate that Western law generally prioritizes justice, legal certainty, and utility as the primary orientations of law, although these three objectives often exist in a dynamic and conflicting relationship. Meanwhile, Islamic law views law not only as serving to maintain social order but also as realizing human welfare holistically through the protection of religion, life, intellect, lineage, and property. This study affirms that the maqāṣid al-syarī‘ah possesses a more comprehensive dimension compared to Western legal purpose theories because it is not only oriented toward worldly interests but also integrates moral, social, and spiritual dimensions. This article contributes to the development of contemporary Islamic legal philosophy, particularly in fostering a theoretical dialogue between Western legal traditions and the maqāṣid al-syarī‘ah in the context of modern society.